The Effect of Compensation, Position Promotion and Work Environment on Work Morale at Toyota Auto 2000 SM Raja - Frengki Wardiman Pangaribuan; Daud Arifin; Husni Muharram Ritonga (Britain International for Academic Research (BIAR) Publisher, 2022)
Morale is very dependent on the input generated by the employee and the output unit produced by the employee. The purpose of this study was conducted to determine and analyze compensation, promotion and work environment effect on performance partially and simultaneously. The research used is research with quantitative methods. The technique of collecting data in this study was done by distributing questionnaires. The data analysis technique in this study used the classical assumption test, multiple regression, hypothesis testing with SPSS 22 software. The population in this study was 83 employees at Toyota Auto 2000 SM Raja. Based on the results of this study, the significance value of Compensation on Performance based on the t test was obtained at tcount > ttable (3, 857 > 2.001). Thus Ho is rejected. The conclusion: Compensation has a positive and significant effect on performance. Based on the results of this study, the significance value of Position Promotion based on the t-test was obtained at tcount > ttable (4.912 > 2.001). Thus H1 is accepted. The conclusion: Promotion has a positive and significant effect on work morale. Based on the t test, it was obtained that tcount > ttable (2,661 > 2,001). Thus H1 is accepted. The conclusion: the work environment has a positive and significant effect on work morale at Toyota Auto 2000 SM Raja. Based on the results of the F test above, the value of Fcount > Ftable is (25,636 > 3.16) (Sig. 0.000 < 0.05), thus H0 is rejected. In conclusion: Compensation